2004
DOI: 10.1128/jvi.78.17.9093-9104.2004
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant Activities of Novel Cytokines, Interleukin-23 (IL-23) and IL-27, for Induction of Hepatitis C Virus-Specific Cytotoxic T Lymphocytes in HLA-A*0201 Transgenic Mice

Abstract: CD8ϩ cytotoxic T lymphocytes (CTLs) recognize virus-derived peptides in association with major histocompatibility complex class I molecules on the surface of antigen-presenting cells and kill the virus-infected target cells. There are a number of evidences showing that CTLs play a central role in the clearance of pathogenic viruses (67). In case of hepatitis C virus (HCV) infection, vigorous HCV-specific CTL responses existed in the persons resolving acute HCV infection (27). In the experimental model, chimpan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
74
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 78 publications
(75 citation statements)
references
References 69 publications
1
74
0
Order By: Relevance
“…Recently, we have found that IL-27 has a potent ability to induce tumor-specific antitumor activity, which is mainly mediated through CD8 ϩ T cells with enhanced CTL activity (11), and also that IL-27 has a potent adjuvant activity for the induction of HCVspecific CTLs (12). Consistent with these two studies indicating that IL-27 augments CTL activity in vivo, we have shown in this study that IL-27 directly acts on naive CD8…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Recently, we have found that IL-27 has a potent ability to induce tumor-specific antitumor activity, which is mainly mediated through CD8 ϩ T cells with enhanced CTL activity (11), and also that IL-27 has a potent adjuvant activity for the induction of HCVspecific CTLs (12). Consistent with these two studies indicating that IL-27 augments CTL activity in vivo, we have shown in this study that IL-27 directly acts on naive CD8…”
Section: Discussionsupporting
confidence: 78%
“…Moreover, we have evaluated the adjuvant activity of IL-27 expression plasmid in the prime-boost immunization consisting of an hepatitis C virus (HCV) core expression plasmid and a recombinant adenovirus-expressing HCV core, and elucidated that IL-27 has a potent adjuvant activity for the induction of HCV-specific CTLs (12). These two studies clearly indicate that IL-27 augments CTL activity in vivo, whereas little is known on the molecular mechanism underlying the augmentation of CTL activity by IL-27.…”
mentioning
confidence: 99%
“…In the study by Lee et al, mRNA levels of p19 were examined whereas Louis et al examined secreted IL-23, which may partially explain the observed discrepancy. In 2004, a study revealed that IL-23 has potent adjuvant effects on induction of epitope-specific cytotoxic T lymphocytes (CTLs) (Matsui, Moriya et al, 2004). The authors found that coadministration of an IL-23 expression plasmid in a prime-boost immunization enhanced the induction of Hepatitis C virus (HCV)-specific CTLs in mice.…”
Section: Il-23 and Hiv Infectionmentioning
confidence: 99%
“…This expression vector encodes the preprotrypsin signal peptide and the 3xFLAG-epitope-tag sequence upstream of the multiple cloning region and, hence, expresses a secreted N-terminal 3xFLAG fusion protein in mammalian cells. Conversely, the murine IL-12 (p3xFLAG-IL-12) and murine IL-23 (p3xFLAG-IL-23) expression plasmids, which include murine single-chain (sc)IL-12 and murine scIL-23 genes, respectively, had previously been constructed (6). The scIL-12 and scIL-23 genes are composed of p40 genetically fused with p35 and p19, respectively (6).…”
Section: Construction Of Recombinant Virusesmentioning
confidence: 99%
“…Conversely, the murine IL-12 (p3xFLAG-IL-12) and murine IL-23 (p3xFLAG-IL-23) expression plasmids, which include murine single-chain (sc)IL-12 and murine scIL-23 genes, respectively, had previously been constructed (6). The scIL-12 and scIL-23 genes are composed of p40 genetically fused with p35 and p19, respectively (6). The biological activity of each single-chain cytokine was shown to be almost similar to that of the native heterodimeric cytokine (4,5).…”
Section: Construction Of Recombinant Virusesmentioning
confidence: 99%